Geochemistry and Weathering Indices of Yedoma and Alas Deposits beneath Thermokarst Lakes in Central Yakutia - Ulrich, Mathias; Jongejans, Loeka L.; Grosse, Guido; Schneider, Birgit; Opel, Thomas; Wetterich, Sebastian; Fedorov, Alexander N.; Schirrmeister, Lutz; Windirsch, Torben; Wiedmann, Julia; Strauss, Jens (Frontiers in Earth Science, 2021)
Ice- and organic-rich deposits of late Pleistocene age, known as Yedoma Ice Complex (IC), are widespread across large permafrost regions in Northeast Siberia. To reconstruct Yedoma IC formation in Central Yakutia, we analyzed the geochemistry, sedimentology, and stratigraphy of thawed and frozen deposits below two thermokarst lakes in different evolutionary stages (a mature alas lake and a initial Yedoma lake) from the Yukechi site in the Lena-Aldan interfluve. We focused on inorganic geochemical characteristics and mineral weathering in two ~17 m long sediment cores to trace syngenetic permafrost aggradation and degradation over time. Geochemical properties, element ratios, and specific weathering indices reflect varying sedimentation processes and seasonal thaw depths under variable environmental conditions. Deeper thaw during the interstadial Marine Isotope Stage (MIS) 3 enabled increasing mineral weathering and initial thermokarst processes. Sedimentological proxies reflect high transport energy and short transport paths and mainly terrestrial sediment supply. The Yedoma formation resulted from fluvial, alluvial and aeolian processes. Low mean TOC contents in both cores contrast with Yedoma deposits elsewhere. Likely, this is a result of the very low organic matter content of the source material of the Yukechi Yedoma. Pronounced cryostructures and strongly depleted pore water stable isotopes show a perennially frozen state and preserved organic matter for the lower part of the Yedoma lake core, while changing permafrost conditions, conditions promoting weathering, and strong organic matter decomposition are suggested by our proxies for its middle and upper parts. For the alas lake core, less depleted water stable isotopes reflect the influence of recent precipitation, i.e. the infiltration of rain and lake water into the unfrozen ground. The FENG, MIA(R), and ICV weathering indices have proven to be promising proxies for the identification of conditions that promote mineral weathering to different degrees in the stratigraphy of the thawed and frozen Yedoma deposits, for which we assume a rather homogeneous chemical composition of the parent material. Our study highlights that the understanding of environmental conditions during Yedoma formation and degradation processes by specific geochemical proxies is crucial for assessing the potential decomposition and preservation of the frozen and unfrozen Yedoma inventories.